2019
DOI: 10.3389/fneur.2019.00834
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Long-Term Hippotherapy on the Walking Ability of Children With Cerebral Palsy and Quality of Life of Their Caregivers

Abstract: Background: Cerebral palsy (CP) is a permanent motor disorder that occurs at birth or during early infancy. Despite advances in fetal and maternal medicine, the incidence of CP remains high. Hippotherapy has gradually been recognized as an excellent rehabilitation tool for children with CP. However, a scientific basis for how it achieves long-term functional improvements or provides additional benefits to patients' caregivers remains unknown. Objectives: We performed a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…Thus, riding a horse leads to bilateral, continuous, and symmetrical movement patterns that stimulate muscle fibers and positively affect the control of posture and balance [ 43 ]. Furthermore, its practice requires the participation of the whole body and, therefore, it contributes to changes in muscle tone and motor coordination [ 56 ]. For this reason, this type of therapy has been used as a complementary strategy to reduce spasticity and improve motor skills [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, riding a horse leads to bilateral, continuous, and symmetrical movement patterns that stimulate muscle fibers and positively affect the control of posture and balance [ 43 ]. Furthermore, its practice requires the participation of the whole body and, therefore, it contributes to changes in muscle tone and motor coordination [ 56 ]. For this reason, this type of therapy has been used as a complementary strategy to reduce spasticity and improve motor skills [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary goals are to promote function, empower families, improve fitness, promote participation in fun activities, and enhance children’s opportunities to develop meaningful peer connections 35 . Some studies found that hippotherapy improved social and behavioural aspects in children with autism spectrum disorder, 36 quality of life of the caregivers of children with CP, 4 and participation of children with CP 37 . Hippotherapy has been considered an intervention that could enhance participation, while providing valuable physical exercise, through the interaction of the children with the animal and other children 37 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no clear benefit on function (mobility) with yoga versus usual care or waitlist control. 9,21,[50][51][52] In CP studies, balance [53][54][55] and function (multifactorial) 53,54,[56][57][58][59][60] may be improved with hippotherapy compared with usual care or waitlist control. Motion gaming may also improve balance in participants with cerebral palsy compared with usual care or motion gaming using a mouse.…”
Section: Postural Control or Balance Interventions Included Balance Exercises Hippotherapy Taimentioning
confidence: 99%